LITERATURE REVIEW : INDEKS MASA TUBUH, DURASI DAN POSTUR KERJA BERDIRI DENGAN KELUHAN NYERI BAHU DAN KAKI PADA PEKERJA - Simarmata, Monica Rosa; Wahyuni, Ida; Ekawati, Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Shoulders and leg complaints are part of the musculoskeletal disorders that can be felt by workers and caused by themselves and their workplaces. Some factors that known could caused shoulders and leg complaints are body mass index, work duration, and standing work posture. The aim of this study was to analyze the relation between body mass index, work duration and standing work posture with shoulders and leg complaints to workers. Using quantitative literature study, 15 articles which consist of 12 national articles and 3 international articles that related to the topic were analyzed Literature is done online through several websites or internet sites such as ScienceDirect, PUBMed and Google Scholar. The results of this study revealed the following (1) shoulders complaints were escalated by work duration andwork posture, (2) leg complaints were escalated by body mass index, work duration and standing work posture.